Preparation and heat treatment method of high-strength and high-toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy

By using selective laser melting technology in La-Fe-Co-Si alloy to dopant Cu elements and perform annealing + quenching treatment, the problem of poor strength and toughness of the alloy is solved, significantly improving its elongation and compression strength, and improving magnetic refrigeration Application potential of materials.

CN119159095APending Publication Date: 2024-12-20SHENYANG LIGONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411272562.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

La-Fe-Co-Si alloy is subject to poor toughness in magnetic refrigeration machines, which leads to lattice distortion and dislocation accumulation during magnetic phase transition, forming cracks, limiting its wide application in magnetic refrigeration machines. .

Method used

Selective laser melting technology is used to dopant Cu elements in La-Fe-Co-Si alloy to construct a plastic eutectic interface, and the interface structure is regulated through annealing + quenching heat treatment to improve the strength and toughness of the alloy.

Benefits of technology

It significantly improves the elongation and compression strength of La-Fe-Co-Si alloy, improves the machining property, and the compression strength reaches 880MPa~930MPa, with an elongation of 5%~6%, which is much higher than that of La-Fe cast by other methods. -Co-Si alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119159095A_ABST
    Figure CN119159095A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alloy preparation, in particular to a preparation and heat treatment method of a high-strength and high-toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy. Under the argon protective atmosphere, the Cu element is doped into the La-Fe-Co-Si alloy through the selective laser melting 3D printing technology, and then the high-strength and high-toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy is obtained through annealing and quenching heat treatment. The selective laser melting method is firstly used for doping the Cu element into the alloy to construct a plastic eutectic interface, the alloy is subsequently subjected to annealing and quenching heat treatment to regulate and control the interface structure, and therefore the problems that the La-Fe-Co-Si magnetic refrigeration alloy is poor in obdurability and the like are effectively solved, the ductility and the compression strength of the alloy are remarkably improved, and the mechanical property of the alloy is improved. And the machinability of the alloy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy preparation, and in particular to a preparation and heat treatment method of a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy. Background Art

[0002] Since the 21st century, space refrigeration has become the cornerstone of the development of aerospace, medical, electronics and other fields. Among them, magnetic refrigeration technology, as an environmentally friendly, low-carbon solid refrigeration technology, is extremely feasible and has application potential in ultra-low temperature zones (<1K), low temperature zones (such as nuclear magnetic resonance imaging) and room temperature zones (such as refrigerators). This technology can improve the refrigeration efficiency by about 30% without using chemical refrigerants. Its basic principle is to use the magnetocaloric effect of magnetic refrigeration materials to cool the device, that is, to use the temperature change caused by the change of internal magnetic moment during the demagnetization process of the material for refrigeration. La-Fe-Co-Si alloy has the advantages of easy adjustment of the working temperature range, no toxic and harmful elements, high magnetocaloric effect and small hysteresis loss. Therefore, it is one of the most promising room temperature magnetic refrigeration materials. However, in the actual test process, it was found that the key problem limiting the widespread application of this alloy in magnetic refrigerators is poor strength and toughness. The reason is that the lattice distortion effect (~1.1vol.%) accompanied by the alloy during the magnetic phase change process easily generates and accumulates dislocations at the grain boundaries, resulting in stress concentration, cracks, and ultimately failure.

[0003] At present, the most common solution is to prepare a composite material by physically combining La-Fe-Co-Si alloy with plastic materials such as resin, pure metal and solder. However, due to the differences in thermal expansion coefficient, elastic modulus and wettability between the two materials, defects such as pores and cracks are easily formed at the interface of the composite material, and the interface bonding force is poor, which does not effectively improve the problem of poor strength and toughness of the alloy. Establishing a physical interface in La-Fe-Co-Si alloy does not fundamentally improve the generation and accumulation of dislocations, and it is difficult to achieve an improvement in mechanical properties. Therefore, it is urgent to develop a preparation method that significantly improves the strength and toughness of La-Fe-Co-Si alloy. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation and heat treatment method of a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy. First, the Cu element is doped into the alloy by the selective laser melting method to construct a plastic eutectic interface, and then the alloy is annealed + quenched to regulate the interface structure, thereby effectively solving the problems of poor strength and toughness of the La-Fe-Co-Si magnetic refrigeration alloy, so that the elongation and compression strength of the alloy are significantly improved, and the machinability of the alloy is improved.

[0005] The technical solution of the present invention is:

[0006] A preparation and heat treatment method for a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy. In an argon protective atmosphere, the Cu element is doped into the La-Fe-Co-Si alloy by using a selective laser melting 3D printing technology, and then the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy is obtained by annealing + quenching heat treatment.

[0007] The preparation and heat treatment method of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, in terms of atomic percentage, the composition of the La-Fe-Co-Si alloy is La 6.8 Fe 82.8 Co 5.5 Si 4.9 .

[0008] The preparation and heat treatment method of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy comprises the following steps:

[0009] (1) Preparation of La by aerosol method 6.8 Fe 82.8 Co 5.5 Si 4.9 powder

[0010] Before preparing powder by aerosol method, La with the same composition was prepared by arc melting method. 6.8 Fe 82.8 Co 5.5 Si 4.9 Alloy bars: First, grind and clean the raw materials to remove the oxide scale on the surface of the pure metal raw materials. Use a high-precision electronic balance to weigh each metal raw material according to the nominal composition of the alloy. Put the weighed metal raw materials into the melting furnace, put the easily oxidized La and the Si with a higher melting point in the lower layer, put Co in the middle layer, and put Fe with a lower melting point in the upper layer. Evacuate the melting furnace to reduce the pressure in the furnace to 10 -3 Pa, high-purity argon gas was injected at the same time, and the alloy was homogenized by electromagnetic stirring. The whole melting process was repeated 4 to 5 times to obtain La 6.8 Fe 82.8 Co 5.5 Si 4.9 Alloy rods are then heated to liquid state and injected into a tundish located above the atomizing nozzle. The metal liquid flows out from the hole at the bottom of the tundish and meets the ejected high-speed gas when passing through the nozzle and is atomized into fine liquid, which is then solidified to form powder.

[0011] (2) Cu powder and La powder were mixed by mechanical mixing method. 6.8 Fe 82.8 Co 5.5 Si 4.9 Powder mixing

[0012] Cu powder and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The powder is mixed evenly by mechanical mixing method to make La 6.8 Fe 82.8 Co 5.5 Si 4.9 A layer of Cu particles is uniformly adsorbed on the powder surface;

[0013] (3) The Cu element is incorporated into the La-Fe-Co-Si alloy structure by selective laser melting

[0014] The Cu and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The mixed powder was 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process was carried out under an argon protective atmosphere to prevent the powder from oxidizing.

[0015] (4) Annealing + quenching heat treatment technology is used to improve the elongation and compressive strength of La-Fe-Co-Si rare earth magnetic refrigeration alloy.

[0016] The preparation and heat treatment method of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, in step (1), the high-speed gas used for preparing the powder by aerosol method is argon, the atomizing gas pressure is 3.5-5.0 MPa, and the powder particle size after solidification is 15-53 μm.

[0017] The preparation and heat treatment method of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, in step (2), Cu powder and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The mass ratio of the powders is 1:19.

[0018] In the method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, in step (3), the process of selective laser melting is as follows:

[0019] ① Powder bed preparation: First, a thin layer of powder is evenly spread on the substrate to form a uniform particle bed; ② Laser scanning and melting: A high-energy laser beam is directed to the powder surface, and the laser scans the area according to the set scanning path to selectively melt and fuse the metal particles; ③ Layer-by-layer construction: After each layer is melted and solidified, the substrate is lowered and a new layer of metal powder is evenly spread on the top. The process is repeated, and the laser scans and melts each layer to bond the newly melted material to the previous layer. This layer-by-layer construction process continues until the entire ingot is created.

[0020] The preparation and heat treatment method of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy is as follows: during the selective laser melting process, Cu is filled into La 6.8 Fe 82.8 Co 5.5 Si 4.9 The pores between the particles increase the density of the alloy and react with the La element to form a plastic eutectic interface, thereby improving the strength and toughness of the alloy.

[0021] In the method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, in step (3), the laser power range of the selective laser melting method is 180W to 270W, the scanning rate is 300mm / s to 450mm / s, the layer thickness is 30μm to 50μm, and the scanning spacing is 0.09mm to 0.12mm.

[0022] The preparation and heat treatment method of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, in step (4), the annealing temperature in the annealing + quenching heat treatment technology is 1323K~1373K, and the quenching treatment is directly performed after keeping warm for 6h~24h, and the medium used for quenching is an ice-water mixture.

[0023] The preparation and heat treatment method of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy regulates the alloy interface structure by annealing temperature and time during the annealing process, so that the structure at the eutectic interface is transformed into a LaCuSi phase and a LaCu2 phase with a close-packed hexagonal structure during the annealing process, thereby achieving second phase strengthening and further improving the strength and toughness of the alloy.

[0024] The design concept of the present invention is:

[0025] The present invention uses the selective laser melting technology to add Cu element into La-Fe-Co-Si magnetic refrigeration alloy to construct a plastic eutectic interface at the grain boundary, and then uses annealing + quenching technology to heat treat the alloy, which can greatly improve the elongation and compression strength of the alloy. The composition of the magnetic refrigeration alloy is La 6.8 Fe 82.8 Co 5.5 Si 4.9In the non-equilibrium rapid solidification process of selective laser melting, the solidification rate of the whole process is >10 6 K / s, the grain size is greatly reduced, which can play a role in grain refinement. In addition, since the melting point of Cu (1357K) is lower than that of La 6.8 Fe 82.8 Co 5.5 Si 4.9 The melting point of Cu is 1773K. During the selective laser melting process, Cu will melt before La. 6.8 Fe 82.8 Co 5.5 Si 4.9 Melting occurs, which can not only effectively fill La 6.8 Fe 82.8 Co 5.5 Si 4.9 The pores between particles increase the density of the alloy and can also form a plastic eutectic interface with the La element to improve the strength and toughness of the alloy. In the subsequent annealing + quenching process, the interface structure is designed by adjusting the annealing temperature and time to form fine LaCuSi and LaCu2 plastic phases, achieving second phase strengthening, and further improving the strength and toughness of the alloy.

[0026] The advantages and beneficial effects of the present invention are as follows:

[0027] 1. The present invention provides a method for preparing and heat treating a high-strength and toughness rare earth magnetic refrigeration alloy, wherein the alloy comprises La 6.8 Fe 82.8 Co 5.5 Si 4.9 It uses the non-equilibrium rapid solidification forming process of selective laser melting to refine the grains and produce fine grain strengthening. At the same time, it uses the La-Cu eutectic reaction to form a plastic eutectic interface to improve the strength and toughness of the alloy, and uses the low melting point of Cu to effectively fill La 6.8 Fe 82.8 Co 5.5 Si 4.9 The pores between powders increase the density. The subsequent annealing + quenching method is used to regulate the interface structure, form fine LaCuSi and LaCu2 plastic phases, achieve second phase strengthening, and further improve the strength and toughness of the alloy. The final alloy has a compressive strength of 880MPa to 930MPa and an elongation of 5% to 6%, which is much higher than La-Fe-Co-Si alloys cast by other methods.

[0028] 2. The preparation and heat treatment methods of the high-strength and toughness rare earth magnetic refrigeration alloy of the present invention can be applied in the field of magnetic refrigeration, providing theoretical and technical support for improving the toughness and processability of magnetic refrigeration materials in magnetic refrigerators. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following is a brief introduction to the drawings required for use in the embodiment. It can be seen that the following drawings are only part of the experimental embodiment. For ordinary technicians in this field, the following simple diagrams can also be used to obtain other related drawings based on these drawings without paying any creative work.

[0030] Figure 1 Schematic diagram of the process of doping Cu element into La-Fe-Co-Si alloy by selective laser melting in Example 1 of the present invention, Cu powder, La 6.8 Fe 82.8 Co 5.5 Si 4.9 Scanned images of powder and powder blend, and macroscopic images of the final alloy ingot.

[0031] Figure 2 The backscattered scanning images of the cross section and longitudinal section of the Cu-doped La-Fe-Co-Si alloy ingot in Example 1 of the present invention are shown. The grains contain a dendrite structure composed of α-Fe and rich La, the grain boundaries are eutectic interfaces, and the selective melting process of the alloy is: laser power 270W, scanning speed 400mm / s, scanning spacing 0.09mm, and layer thickness 30μm.

[0032] Figure 3 The transmission image of the eutectic interface in the Cu-doped La-Fe-Co-Si alloy in Example 1 of the present invention. Among them, (a) is a complete transmission image, (b) is a transmission image of the R1 region in (a), (c) is an α-Fe phase, (d) is a LaCuSi phase, the continuous phase and the rod-like phase are LaCuSi and α-Fe phases, respectively, and the selective melting process of the alloy is: laser power 270W, scanning speed 400mm / s, scanning spacing 0.09mm, layer thickness 30μm.

[0033] Figure 4 This is a scanned image of the microstructure of the Cu-doped La-Fe-Co-Si alloy quenched after annealing at 1323K for 12 hours in Example 1 of the present invention. The dark gray phase is the α-Fe phase, and the light gray phase is the La(Fe,Co,Si) phase. 13 phase, the deep white phase (white 1) is LaCuSi phase, the light white phase (white 2) is LaCu2 phase, and the selective melting process of the alloy is: laser power 270W, scanning speed 400mm / s, scanning spacing 0.09mm, and layer thickness 30μm.

[0034] Figure 5-Figure 6The mechanical properties of the Cu-doped La-Fe-Co-Si alloy prepared by selective laser melting (SLM) in Example 1 of the present invention before and after annealing + quenching treatment are compared with the mechanical properties of the cast La-Fe-Co-Si alloy with the same composition. Figure 5 is the compressive stress-strain curve, Figure 6 In order to compare the compressive strength and elongation of Cu-doped La-Fe-Co-Si alloy prepared by SLM after annealing + quenching with those of La-Fe-Co-Si alloy under other casting processes, the selective melting process of the alloy was: laser power 270 W, scanning speed 400 mm / s, scanning spacing 0.09 mm, and layer thickness 30 μm. DETAILED DESCRIPTION

[0035] In the specific implementation process, the preparation and heat treatment method of the high-strength and toughness rare earth magnetic refrigeration alloy of the present invention uses the method of selective laser melting to add Cu element into La-Fe-Co-Si alloy, and then uses the heat treatment method of annealing + quenching to greatly improve the strength and toughness of the alloy, wherein the composition of the magnetic refrigeration alloy is La 6.8 Fe 82.8 Co 5.5 Si 4.9 (at.%).

[0036] The Cu element is doped into the La-Fe-Co-Si rare earth magnetic refrigeration alloy by the method of selective laser melting, and the specific parameters are as follows: the laser power range is 180W~270W, the scanning rate is 300mm / s~450mm / s, the layer thickness is 30μm~50μm, and the scanning spacing is 0.09mm~0.12mm. The annealing + quenching heat treatment technology is subsequently used to improve the strength and toughness of the alloy. The specific parameters are as follows: the annealing temperature is 1323K~1373K, the heat treatment time is 6h~24h, and the cooling medium used for quenching is an ice-water mixture. It should be noted that by further optimizing the process parameters of selective laser melting, the alloy has fewer defects and higher strength and toughness. By processing the La-Fe-Co-Si rare earth magnetic refrigeration alloy within the above parameter range, the strength and toughness of the alloy can be effectively guaranteed. In other embodiments of the present invention, the process parameters can also be adjusted according to demand.

[0037] In order to make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. It is obvious that what is described is only a part of the embodiment, not all of the embodiment. Below, the preparation and heat treatment process of the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy provided by the embodiment of the present invention are specifically described.

[0038] Example 1

[0039] This embodiment provides a preparation and heat treatment process of a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, which is prepared and heat treated by the following method:

[0040] (1) Preparation of La by aerosol method 6.8 Fe 82.8 Co 5.5 Si 4.9 powder

[0041] Before preparing powder by aerosol method, La with the same composition was prepared by arc melting method. 6.8 Fe 82.8 Co 5.5 Si 4.9 Alloy bars: First, grind and clean the raw materials to remove the oxide scale on the surface of the pure metal raw materials. Use a high-precision electronic balance to weigh each metal raw material according to the nominal composition of the alloy. Put the weighed metal raw materials into the melting furnace, put the easily oxidized La and the Si with a higher melting point in the lower layer, put Co in the middle layer, and put Fe with a lower melting point in the upper layer. Evacuate the melting furnace to reduce the pressure in the furnace to 10 -3 Pa, and high-purity argon (volume purity 99.999%) is injected at the same time, and the alloy is homogenized by electromagnetic stirring. The whole smelting process is repeated 5 times to obtain an alloy rod, and then the alloy rod is heated to a liquid state and injected into a tundish located above the atomizing nozzle. The metal liquid flows out from the leak at the bottom of the tundish, meets the ejected high-speed gas (the argon pressure in this embodiment is 4 MPa) when passing through the nozzle, and is atomized into a fine liquid, which is formed into a powder after solidification. The particle size of the powder after solidification is 25 to 53 μm.

[0042] (2) Cu powder and La powder were mixed by mechanical mixing method. 6.8 Fe 82.8 Co 5.5 Si 4.9 Powder mixing

[0043] A small amount of Cu powder and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The powders were mixed evenly by mechanical mixing at a mass ratio of 1:19. 6.8 Fe 82.8 Co 5.5 Si 4.9 A layer of Cu particles is uniformly adsorbed on the powder surface.

[0044] (3) The Cu element is incorporated into the La-Fe-Co-Si alloy structure by selective laser melting

[0045] The Cu and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The mixed powder is 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process is carried out under an argon protective atmosphere to prevent the powder from oxidizing. The specific process is: ① Powder bed preparation: First, a thin layer of powder is evenly spread on the substrate to form a uniform particle bed. The thickness of each layer of powder is 30μm; ② Laser scanning and melting: A laser beam with a power of 270W is guided to the surface of the powder. The laser scans the area according to the set scanning path. The scanning interval is 0.09mm and the scanning speed is 400mm / s. The metal particles are selectively melted and fused; ③ Layer-by-layer construction: After each layer is melted and solidified, the substrate is lowered and a new layer of metal powder is evenly spread on the top. The layer thickness is still 30μm. The process is repeated. The laser scans and melts each layer to bond the newly melted material to the previous layer. This layer-by-layer construction process continues until the entire ingot is created.

[0046] (4) Annealing + quenching heat treatment technology is used to improve the elongation and compressive strength of La-Fe-Co-Si rare earth magnetic refrigeration alloy.

[0047] The alloy ingot prepared by selective laser melting was subjected to annealing + quenching treatment. The annealing temperature was 1323K. After keeping warm for 12 hours, it was directly quenched. The cooling medium used for quenching was an ice-water mixture. The final La-Fe-Co-Si rare earth magnetic refrigeration alloy had an elongation of 6% and a compressive strength of 920MPa.

[0048] Example 2

[0049] This embodiment provides a preparation and heat treatment process of a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, which differs from Embodiment 1 only in that:

[0050] In step (3), Cu and La are melted by selective laser melting. 6.8 Fe 82.8 Co 5.5 Si 4.9 The mixed powder was 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process was carried out under an argon protective atmosphere to prevent powder oxidation. During the laser scanning and melting process, the power of the selective laser melting was 240W. The final La-Fe-Co-Si rare earth magnetic refrigeration alloy had an elongation of 5.4% and a compressive strength of 900.2MPa.

[0051] Example 3

[0052] This embodiment provides a preparation and heat treatment process of a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, which differs from Embodiment 1 only in that:

[0053] In step (3), Cu and La are melted by selective laser melting. 68 Fe 828 Co 55 Si 49 The mixed powder was 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process was carried out under an argon protective atmosphere to prevent powder oxidation. During the laser scanning and melting process, the scanning rate of the selective laser melting was 450mm / s. The final La-Fe-Co-Si rare earth magnetic refrigeration alloy had an elongation of 5.95% and a compressive strength of 915MPa.

[0054] Example 4

[0055] This embodiment provides a preparation and heat treatment process of a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, which differs from Embodiment 1 only in that:

[0056] In step (3), Cu and La are melted by selective laser melting. 6.8 Fe 82.8 Co 5.5 Si 4.9 The mixed powder was 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process was carried out under an argon protective atmosphere to prevent powder oxidation. During the laser scanning and melting process, the scanning spacing of the selective laser melting was 0.1mm. The final La-Fe-Co-Si rare earth magnetic refrigeration alloy had an elongation of 5.45% and a compressive strength of 915MPa.

[0057] Example 5

[0058] This embodiment provides a preparation and heat treatment process of a La-Fe-Co-Si rare earth magnetic refrigeration alloy, which differs from Embodiment 1 only in that:

[0059] In step (3), Cu and La are melted by selective laser melting. 6.8 Fe 82.8 Co 5.5 Si 4.9The mixed powder was 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process was carried out under an argon protective atmosphere to prevent powder oxidation. In the laser scanning and melting process, the power of the selective laser melting was 160W. The mixed powder of La-Fe-Co-Si rare earth magnetic refrigeration alloy finally obtained did not melt and the ingot failed to form. The reason is that the laser power is too low, and the energy provided is difficult to melt the powder and fuse it, resulting in the failure of the ingot to form.

[0060] Example 6

[0061] This embodiment provides a preparation and heat treatment process of a La-Fe-Co-Si rare earth magnetic refrigeration alloy, which differs from Embodiment 1 only in that:

[0062] In step (3), Cu and La are melted by selective laser melting. 6.8 Fe 82.8 Co 5.5 Si 4.9 The mixed powder was 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process was carried out under an argon protective atmosphere to prevent the powder from oxidizing. In the laser scanning and melting process, the scanning rate of the selective laser melting was 600mm / s. The final elongation of the La-Fe-Co-Si rare earth magnetic refrigeration alloy was only 2.4%, and the compression strength was only 330MPa. The reason is that the scanning rate is too fast, resulting in insufficient energy absorbed by the metal powder, partial melting of the powder particles or failure to melt, and also making it difficult to discharge the gas formed during the melting process of the alloy, which greatly increases the porosity and thus greatly reduces the toughness.

[0063] Example 7

[0064] This embodiment provides a preparation and heat treatment process of a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, which differs from Embodiment 1 only in that:

[0065] In step (4), annealing + quenching heat treatment technology is used to improve the elongation and compressive strength of the La-Fe-Co-Si rare earth magnetic refrigeration alloy. The annealing temperature is 1353K, and the final La-Fe-Co-Si rare earth magnetic refrigeration alloy has an elongation of 5.5% and a compressive strength of 880MPa.

[0066] Example 8

[0067] This embodiment provides a preparation and heat treatment process of a La-Fe-Co-Si rare earth magnetic refrigeration alloy, which differs from Embodiment 1 only in that:

[0068] In step (4), annealing + quenching heat treatment technology is used to improve the elongation and compressive strength of the La-Fe-Co-Si rare earth magnetic refrigeration alloy. The annealing time is 36 hours, and the final elongation of the La-Fe-Co-Si rare earth magnetic refrigeration alloy is 3.5%, and the compressive strength is 480MPa. The reason is that: if the heat treatment time is too long, the grain size of the alloy will increase, and the fine grain strengthening will fail, so the brittleness of the material will increase, and the strength and toughness will decrease.

[0069] Reference Figure 1 As shown, the mechanical powder mixing method can be used to mix Cu and La 6.8 Fe 82.8 Co 5.5 Si 4.9 Mix the powder evenly to make La 6.8 Fe 82.8 Co 5.5 Si 4.9 A layer of nano Cu powder is evenly adsorbed on the surface of the powder. The basic process flow of selective laser melting is to guide a high-energy laser beam to the surface of the powder. The laser scans the area according to the set scanning path to selectively melt and fuse the metal particles. After each layer is melted and solidified, the substrate is lowered and a new layer of metal powder is evenly spread on the top. The process is repeated. The laser scans and melts each layer, bonding the newly melted material to the previous layer until the entire ingot is created.

[0070] Reference Figure 2 As shown in the figure, the Cu-doped La-Fe-Co-Si alloy ingot prepared by selective laser melting has the following structural features in the backscattered images in the cross-sectional and longitudinal sections: the interior of the grain is a fine dendrite structure composed of α-Fe and La-rich phase, and the grain boundary is a eutectic interface rich in La, Cu, and Si.

[0071] Reference Figure 3 As shown, the transmission bright field image of the La, Cu, Si-rich eutectic interface shows that the interface is a rod-shaped eutectic structure composed of a continuous LaCuSi phase and a rod-shaped α-Fe phase, wherein the width of the LaCuSi phase is 0.2μm to 1μm, and the diameter of the α-Fe phase is about 3μm.

[0072] Reference Figure 4 As shown in the figure, there are four phases in the alloy structure after annealing + quenching treatment. During the annealing process, α-Fe and La-rich phase will undergo peritectic reaction to generate La(Fe, Co, Si). 13 phase, and there is some residual α-Fe, so the interior of the grain is La(Fe,Co,Si) 13and α-Fe phase, and the structure at the interface is transformed into LaCuSi phase and LaCu2 phase during annealing. Both phases contribute to the improvement of the strength and toughness of the alloy ingot: LaCuSi phase is a close-packed hexagonal structure, and a large number of basal plane stacking faults inside it can promote twin movement, reduce stacking fault energy, and thus improve plasticity; LaCu2 phase is also a close-packed hexagonal structure, which is similar to La(Fe, Co, Si) 13 There is a semi-coherent interface between the phases, so a large number of dislocations will be formed at the interface, which will promote the coordinated deformation of the two phases and thus improve the strength and toughness of the material.

[0073] Reference Figure 5 As shown in the figure, compared with conventional cast alloy ingots, the method of adding Cu element into La-Fe-Co-Si alloy by selective laser melting can greatly improve the elongation and compressive strength of the alloy. After the ingot is subsequently annealed + quenched, the elongation and compressive strength of the alloy are further improved.

[0074] Reference Figure 6 As shown, the La-Fe-Co-Si alloy prepared by the selective laser melting + annealing + quenching process in the present invention has much higher toughness than the La-Fe-Co-Si alloy prepared by other casting processes.

[0075] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing and heat treating a high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy, characterized in that: Under argon protective atmosphere, Cu element was doped into La-Fe-Co-Si alloy by selective laser melting 3D printing technology, and then high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy was obtained through annealing + quenching heat treatment.

2. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 1, characterized in that: In terms of atomic percentage, the composition of La-Fe-Co-Si alloy is La 6.8 Fe 82.8 Co 5.5 Si 4.9 .

3. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 1 or 2, characterized in that: The steps include: (1) Preparation of La by aerosol method 6.8 Fe 82.8 Co 5.5 Si 4.9 powder Before preparing powder by aerosol method, La with the same composition was prepared by arc melting method. 6.8 Fe 82.8 Co 5.5 Si 4.9 Alloy bars: First, grind and clean the raw materials to remove the oxide scale on the surface of the pure metal raw materials. Use a high-precision electronic balance to weigh each metal raw material according to the nominal composition of the alloy. Put the weighed metal raw materials into the melting furnace, put the easily oxidized La and the Si with a higher melting point in the lower layer, put Co in the middle layer, and put Fe with a lower melting point in the upper layer. Evacuate the melting furnace to reduce the pressure in the furnace to 10 -3 Pa, high-purity argon gas was injected at the same time, and the alloy was homogenized by electromagnetic stirring. The whole melting process was repeated 4 to 5 times to obtain La 6.8 Fe 82.8 Co 5.5 Si 4.9 Alloy rods are then heated to liquid state and injected into a tundish located above the atomizing nozzle. The metal liquid flows out from the hole at the bottom of the tundish and meets the ejected high-speed gas when passing through the nozzle and is atomized into fine liquid, which is then solidified to form powder. (2) Cu powder and La powder were mixed by mechanical mixing method. 6.8 Fe 82.8 Co 5.5 Si 4.9 Powder mixing Cu powder and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The powder is mixed evenly by mechanical mixing method to make La 6.8 Fe 82.8 Co 5.5 Si 4.9 A layer of Cu particles is uniformly adsorbed on the powder surface; (3) The Cu element is incorporated into the La-Fe-Co-Si alloy structure by selective laser melting The Cu and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The mixed powder was 3D printed into an alloy ingot with a size of 4mm×4mm×8mm. The printing process was carried out under an argon protective atmosphere to prevent the powder from oxidizing. (4) Annealing + quenching heat treatment technology is used to improve the elongation and compressive strength of La-Fe-Co-Si rare earth magnetic refrigeration alloy.

4. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 3, characterized in that: In step (1), the high-speed gas used for preparing the powder by the aerosol method is argon, the atomizing gas pressure is 3.5 to 5.0 MPa, and the powder particle size after solidification is 15 to 53 μm.

5. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 3, characterized in that: In step (2), Cu powder and La 6.8 Fe 82.8 Co 5.5 Si 4.9 The mass ratio of the powders is 1:

19.

6. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 3, characterized in that: In step (3), the process of selective laser melting is as follows: ① Powder bed preparation: First, a thin layer of powder is evenly spread on the substrate to form a uniform particle bed; ② Laser scanning and melting: A high-energy laser beam is directed to the powder surface, and the laser scans the area according to the set scanning path to selectively melt and fuse the metal particles; ③ Layer-by-layer construction: After each layer is melted and solidified, the substrate is lowered and a new layer of metal powder is evenly spread on the top. The process is repeated, and the laser scans and melts each layer to bond the newly melted material to the previous layer. This layer-by-layer construction process continues until the entire ingot is created.

7. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 6, characterized in that: During the selective laser melting process, Cu is filled into La 6.8 Fe 82.8 Co 5.5 Si 4.9 The pores between the particles increase the density of the alloy and react with the La element to form a plastic eutectic interface, thereby improving the strength and toughness of the alloy.

8. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 3, characterized in that: In step (3), the laser power range of the selective laser melting method is 180W to 270W, the scanning rate is 300mm / s to 450mm / s, the layer thickness is 30μm to 50μm, and the scanning spacing is 0.09mm to 0.12mm.

9. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 3, characterized in that: In step (4), the annealing temperature in the annealing + quenching heat treatment technology is 1323K ~ 1373K, and the quenching treatment is directly performed after keeping warm for 6h ~ 24h, and the medium used for quenching is an ice-water mixture.

10. The method for preparing and heat treating the high-strength and toughness La-Fe-Co-Si rare earth magnetic refrigeration alloy according to claim 9, characterized in that: During the annealing process, the alloy interface structure is regulated by annealing temperature and time, so that the structure at the eutectic interface is transformed into LaCuSi phase and LaCu2 phase with close-packed hexagonal structure during the annealing process, realizing second phase strengthening and further improving the strength and toughness of the alloy.

Citation Information

Cited By

  • Preparation method for rapidly obtaining La-Fe-Co-Si rare earth magnetic refrigeration alloy with high magnetocaloric performance

    CN120624875A

  • A method for rapidly preparing La-Fe-Co-Si rare earth magnetic refrigeration alloys with high magnetocaloric properties

    CN120624875B